Dimensions of Fuelwood Problems of U.P. Hills and Solutions Thereof - Maithani, G. P. (Indian Forester, 1994)
U.P. Hill Region forests are fast degrading. Though this is causing many problems but fuelwood scarcity is most acute. In rural areas fuelwood demand is estimated to be about 3.5million tonnes. Most of it stands as deficit and met through irregular removals. The lands and funds required to meet the deficit by raising plantations are rather physical impossibility. In addition to plantations both inside and outside forestry, socio-economic development and providing alternate sources of energy have been suggested. Yields from the forests should be assigned for meeting local rural needs. Efficient protection and management of the existing forests should be aimed at for increasing their productivity. Efficient and just distribution systems and participation of local people in creation and management of assets have been emphasized. Some tree and shrub species have been suggested for raising fuelwood crops both in the forests and agri-ecosytems. Study of the problem in proper perspective and carrying out research thereon need proper and adequate attention. Linking firewood problem with over all energy programme has been indicated. Eco-system diagnosis and cure approach should be adopted. Some policy and technical aspects pertaining to forest management in general and fuelwood supply in particular have been given.